PROSPECTS OF UKRAINIAN-POLISH HUMANITARIAN COOPERATION - Тарасенко, В. (Київський національний університет імені Т. Шевченка, 2024)
The article aims to analyse the current state and future prospects of humanitarian cooperation between Ukraine and Poland against the background of Russia's fully-fledged aggression. The call for the formation of a unified Ukrainian-Polish cultural and informational space as a tool for countering the Russian expansionist and imperial space in the course of the cognitive warfare is emphasised. Moreover, the authors86argue that in addition to the significant intensification of cooperation between Kyiv and Warsaw in the military and political, military and technical, economic and financial domains, humanitarian cooperation between these neighboring countries will become one of the drivers of the European integration of Ukraine. The research acknowledges the increasing mutual interest in the study of languages, cultures and traditions of the Ukrainian and Polish peoples, the reinvigoration of cooperation in the educational and media fields, the development of cultural and public diplomacy.

У статті досліджуються сучасний стан та перспективи гуманітарної співпраці України та Польщі на тлі повномасштабної агресії Росії. Зазначено необхідність формування єдиного україно-польського культурно-інформаційного простору як інструменту протидії російському експансіоністсько-імперському простору в перебігу когнітивної війни. Автор також відзначає, що окрім помітного посилення співпраці Києва та Варшави у воєнно-політичній, військово-технічній, економічній та фінансовій сферах, гуманітарна співпраця країн-сусідів стане одним із драйверів європейської інтеграції України. Дослідження підтверджує взаємне зростання зацікавленості вивченням мов, культур, традицій українського та польського народів, активізацію співпраці в освітній діяльності та медіасферах, розвиток культурної й публічної дипломатії.
УКРАЇНСЬКО-ПОЛЬСЬКА ГУМАНІТАРНА СПІВПРАЦЯ: СУЧАСНИЙ СТАН ТА ПЕРСПЕКТИВИ
Keywords: Ukraine; Poland; Ukrainian-Polish relations; European integration; arts and humanities; media; culture; education; Ukraine; Poland; Ukrainian-Polish relations; European integration; arts and humanities; media; culture; education; Україна; Польща; україно-польські відносини; євроінтеграція; гуманітарна сфера; медіа; культура; освіта; Україна; Польща; україно-польські відносини; євроінтеграція; гуманітарна сфера; медіа; культура; освіта